Designing Waqf Funding in the Forestry Sector: Addresses a Gap in Islamic Philanthropy and Sustainability - Firdan Thoriq Faza (At-Taradhi Jurnal Studi Ekonomi, 2025)
The main objective of this research is to formulate an integrated financing model that supports the sustainable management of waqf forests. This research uses a qualitative approach through in-depth interviews with experts and secondary data collection from various relevant sources. The proposed model emphasizes the formation of the collaborative funding model between waqif and nazhir in sustainable waqf forest management as the main operational framework. The utilization of waqf assets is directed towards waqf forest development by strengthening the role of nazhir as a manager who maintains the ecological mandate and asset productivity. In this scheme, commodities produced from waqf forests through assisted farmer groups are handed over to nazhir to be managed, distributed, and marketed to the market and donors. This research is expected to offer innovative solutions in the management of waqf forest assets that are more productive through synergy between stakeholders and optimization of available resources.